Beyond Error Analysis: Solving EFL Student Writing Problems in Accuracy - Lestari Setyowati (Universitas Muhammadiyah Ponorogo, 2015)
There a is a common assumption that a good piece of writing is often seen from its flawless grammar. Thus, in the world of academic writing, accuracy always becomes the main concern of any writing teachers . Giving feedback , therefore, becomes necessary since teachers could not put aside and disregard grammar. This article is intended to describe different types of Corrective Feedbacks, and type of Corrective Feedbacks which are effective to reduce learners error in L2 writing based on some research findings, and how to use it to promote its effectiveness. In the end of the article, some suggestions are also addressed to the English teacher based on the research results in CF.